Understanding knowledge, perception, and willingness of non-invasive prenatal testing for fetal aneuploidy: a survey among Chinese high-risk pregnant women - Zhao, Yi; Xue, Zhu; Geng, Yarui; Zhu, Jie; Hu, Maidan; Jiang, Minmin (Frontiers in Medicine, 2023)
Objectives Non-invasive prenatal testing (NIPT) is utilized for screening the likelihood of fetal aneuploidy, presenting the benefits of non-invasiveness, high sensitivity, and specificity. Its application in prenatal screening has become ubiquitous. The inquiry into how pregnant women comprehend and determine NIPT screening strategies is paramount. Regrettably, there has been a dearth of research on this subject in China. Consequently, this study scrutinizes pregnant women’s cognizance and perspectives concerning NIPT, furnishing a foundation for advancing its judicious implementation. Methods From February 2021 to December 2022, a questionnaire survey was conducted among pregnant women receiving prenatal care and screening at the Women’s Hospital, School of Medicine, Zhejiang University, who were randomly selected from a pool of individuals exhibiting a high risk of fetal aneuploidy on serological screening. The survey aimed to gather data on participant characteristics, knowledge, perception, and willingness concerning NIPT. The study employed chi-square and Kruskal Wallis tests to analyze subgroup differences. Results A total of 226 valid questionnaires were obtained. 83.2% of women pregnant women identified as high risk by serological screening would opt for NIPT, with 66.4% indicating that they would prefer NIPT for fetal aneuploidy screening in future pregnancies. These findings suggest a notable willingness among pregnant women to undergo NIPT. Additionally, the results suggest that various factors, including place of residence, educational level, family income, causes of abortion, and conception method, influence pregnant women’s knowledge about NIPT Accordingly, the level of NIPT knowledge varies among pregnant women. Conclusion The survey generally revealed that pregnant women were strongly inclined to select NIPT; however, expectant Chinese mothers possess limited knowledge and perception regarding this screening method for fetal aneuploidy. Therefore, the government must implement effective measures to augment public awareness of fetal aneuploidy screening and encourage the judicious utilization of NIPT.